Immediate Effects of Functional Strength Training on Dynamic Balance in Individuals with Unilateral Knee Osteoarthritis - Mehta, Pramod Kumar Singh; Yadav, Pooja; Mandal, Sonam; Baral, Saroj (Journal of Nobel Medical College, 2025)
Background: Knee osteoarthritis causes discomfort, diminished proprioception, and impaired dynamic balance, which can limit daily activities. Exercise continues to be an important part of OA care; however, the immediate effects of a single session of functional strength training on balance and pain are unknown. The purpose of this study was to assess the immediate effects of one session of functional strength exercise on dynamic balance and pain in people with unilateral knee osteoarthritis. Materials and Methods: The quasi-experimental one-group pre-post study design was used. The study included 39 adults who had been diagnosed with unilateral knee OA using Altman clinical criteria. Each participant did one functional strength training session lasting 30-40 minutes. The Star Excursion Balance Test (SEBT) was used to assess dynamic balance before and after the intervention in all eight directions. The Visual Analogue Scale (VAS) was used to quantify pain intensity. Baseline demographic data, as well as the Knee Injury and Osteoarthritis Outcome Score (KOOS), were collected. SEBT reach distances were adjusted for leg length. Paired t-tests were used to examine pre-post comparisons, with a significance level of p < 0.05. Results: Following the exercise session, all subjects showed statistically significant improvements in SEBT reach distances across all eight directions in both the injured and unaffected limbs. The afflicted limb improved more significantly, indicating improved neuromuscular activation and postural control. Pain levels indicated by VAS were significantly lower after intervention. KOOS scores indicated intermediate functional capacity, with higher scores in activities of daily living and lower scores in sports and quality of life domains. Conclusion: A single session of functional strength training resulted in immediate and significant improvements in dynamic balance and pain reduction in those with unilateral knee osteoarthritis. These data support the clinical use of functional strength training as an effective immediate intervention in knee osteoarthritis rehabilitation.